EFEKTIVITAS PELAKSANAAN MUTASI PEGAWAI NEGERI SIPIL (PNS) DI BADAN KEPEGAWAIAN, PENDIDIKAN, DAN PELATIHAN KABUPATEN KUDUS - Ana Aqidatun Niswah; Muhammad Qoes Atieq (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effectiveness of the implementation of mutations in the Personnel, Education and Training Agency of Kudus Regency. In this study using data collection methods obtained through interviews, observation, and literature study. Techniques Data analysis was carried out using qualitative methods through three stages, including data reduction, data presentation, and drawing conclusions. The results showed that the implementation of mutations in the Personnel, Education and Training Agency of Kudus Regency was not yet fully effective because some of the dominant obstacles came from internal human resources